Multi-sensor Satellite Pan-sharpening based on IHS and Window Pseudo Wigner Distribution Integrated Approach: Application to WorldView-2 Imagery. (2nd April 2016) - Rajput, Upendra Kumar; Ghosh, Sanjay Kumar; Kumar, Anil
ABSTRACT: This paper proposes a new approach to fuse high spatial resolution panchromatic (PAN) image with a low spatial resolution multispectral (MS) image, based on the joint use of intensity-hue-saturation (IHS) and Window Pseudo Wigner Distribution (WPWD), with a motive to reduce the spectral distortion problem of IHS technique. This approach utilises the IHS transform to fuse high-resolution spatial information into the low-resolution MS images, and uses the WPWD to reduce the colour distortion, in the way of generating a new high-resolution PAN image that highly correlates with the intensity image of the IHS transform. The new PAN image is, then, used to replace the intensity image for an inverse IHS transform. The proposed hybrid technique has been compared with the existing hybrid techniques in terms of different fusion rules, computational time, qualitative and different quantitative parameters. The very high resolution satellite dataset, especially, WorldView-2 sensor, which provides data at submeter level has been taken for the pan-sharpening. Analysis of results proved that the concept of proposed IHS and WPWD integration using different fusion rules works well and gives a good trade-off between the enhancement of spatial resolution and preservation of spectral information, along with balanced computational time, when compared to IHS, IHS-DWT, IHS-SWT and IHS-NSCT fusion techniques.